Plateau hypoxia improves tumor immune microenvironment and inhibits subcutaneous tumor growth of colorectal cancer - ZHAO Sijie; WANG Meng; GAO Yuan (陆军军医大学学报)
Objective To investigate the effects of plateau hypoxia on the growth and tumor microenvironment of colorectal carcinoma in vivo.Methods‍　‍A total of 16 male BALB/C mice （6 weeks old， weight 18-20 g） were randomly divided into plateau hypoxic group and plain normoxic group， with 8 mice in each group， while 14 male C57BL/6 mice were grouped in same way， with 7 mice in each group. The mice in the plateau hypoxic group were housed in a low-pressure oxygen （10%） chamber to simulate an altitude of approximately 5 600 m， while the mice of the other group was maintained in SPF-grade normal atmospheric conditions （21% oxygen， at an altitude of about 300 m）. Colorectal tumor MC38 cells and colon adenocarcinoma CT26 cells were subcutaneously implanted into C57BL/6 mice and BALB/C mice， respectively to construct subcutaneous tumor-bearing mouse models. Then the tumor size and weight were measured in 4 groups of mice. After the tumor tissues， spleen and blood samples were collected in the C57BL/6 mice. Flow cytometry was used to determine the percentages of macrophages， T lymphocytes， IFN-γ+ T lymphocytes， and myeloid-derived suppressor cells （MDSC）. The differences in these immune cells were compared between the cells from the plateau hypoxic group and those from the plain normoxic group. Results‍　‍The weight of subcutaneous tumor mass was significantly inhibited in both C57BL/6 and BALB/C mice from the plateau hypoxic group than those from the 2 plain normoxic groups （0.17 vs 0.09 g， 1.38 vs 0.51 g， P<0.01）. When compared with the immune cells from the tumor mass of the plain normoxic C57BL/6 mice， the percentage of M2-type macrophages was reduced in the tumor tissue from the plateau hypoxic mice（22.13% vs 15.90%， P<0.05）， so was that of MDSC （2.06% vs 1.05%， P<0.01）， particularly in the monocytic （M）-MDSC subgroup （60.97% vs 41.13%， P<0.01）. While， no significant change was observed in the proportion of the polymorphonuclear （PMN）-MDSC subgroup （10.97% vs 9.70%， P>0.05）. Additionally， the percentage of CD4+ T cells was significantly reduced （48.70% vs 41.93%， P<0.05）， whereas that of CD8+ T cells was obviously increased （41.25% vs 51.18%， P<0.05）， along with a notable rise in the proportions of IFN-γ+ T， IFN-γ+ CD4+ T and IFN-γ+ CD8+ T cells （28.58% vs 59.65%， 23.33% vs 53.65%， 36.9% vs 66.48%， P<0.01）. However， between the peripheral blood samples of the 2 groups of C57BL/6 mice， the proportions of M1-type macrophages and CD4+ T cells were reduced （84.98% vs 78.43%， 5.86% vs 4.01%， P<0.01）， and those of MDSC and PMN-MDC were increased （4.47% vs 16.43%， 36.56% vs 62.97%， P<0.01）. In the spleen tissues， notable decreases were observed in the proportions of CD8+ T cells and IFN-γ+ CD8+ T cells between the 2 groups （33.05% vs 27.68%， 5.13% vs 1.58%， P<0.01）. Conclusion Plateau hypoxia improves the immune response within the tumor microenvironment， and inhibits subcutaneous tumor growth of colorectal cancer， but suppresses systemic immune response.